The Stylistics phenomenon of Ahmad Syauqi’s Poetry “The Noah’s Ark” (Semantic analysis) - Abdul Hafidz Zaid; Alif Cahya Setiyadi; Tyas Pradhita Astari (At-Ta'dib, 2020)
The poetic tale is obviously considered as the high-level literary of the fine arts in the Arab art tradition. This is because of its inner factors that firmly influence the reader and audient apprehension and imaginativeness which, then, establish the thinking perception. One of the upmost examples of this story is the tales of the Prince of Poets ‘Ahmed Syauqy, the pioneer of the poetic tale in the modern era with consists of more than fifty five tales including the Noah’ Ark. This story is characterized by outstanding beautiful poetic style, which varying from the sounds to significance of the story. For this reason, this study aims to analyze semantically the stylistics side of the story. With regards to the methodology, this study primarily utilizes the descriptive methods with chiefly employees the contemporary semantic for analyzing the semantic phenomenon of this literary art. In the final result of this study are primarily encompasses two focuses; the semantic fields and the intertextuality of the story. The observation results variation of the semantic fields occurrence in this story that literalized in semantic fields on the animals, the silent nature, the feelings and traits, the locations, and parts of the body. Furthermore, this story contains two basic intertextuality stylistics, both are: external intertextuality derived from the Holy Qur’an and the internal intertextuality from the story of Noah's Ark its self.